EKONOMI PERDAMAIAN DAN HUBUNGAN ISRAEL-YORDANIA - , Rully Yuliardi Achmad; , Drs. Muhadi Sugiono, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research is concern with peace economy concept as the basic of peace agreement between Israel and Jordan. Some pundits believe that Israel- Jordan Peace Treaty 1994 is the brightest side of the prospect of Middle East peace process. Peace Economy played major role in maintaining peacebuilding since Israel government and The Hashemite Kingdom of Jordan agreed to established Qualifying Industrial Zone (QIZ) that adopted Special Economic Zone concept and Jordan Rift Valley (JRV) such regional development project, as the main economic and development cooperation for both countries. QIZ project was the idea from Omar Salah one of Jordan entrepreneur, and its also supported by businessman community in Israel led by Dov Lautmann and Danny Gillerman. At the same time, there are significance chances of conflict pattern which is not only involving between state and state, but also intra state war, these circumstances bringing new paradigm for conflict resolution, to embedding economic cooperation on clause of accords as new approachment in peacemaking process. The presence of QIZ and JRV as joint project of Israel and the Jordanian government which lies at the southern border had a positive impact on the progress of Arab-Jewish state relations. The equation of interests by Israeli and Jordanian on water desalination, trade cooperation, and development cooperation has been fostered to the peaceful relations between the two countries. The role of the businessman is very significant because it has given a positive signal to decision-makers, which implies that multilateral cooperation is possible to implement. Not only emerged a living harmony among nations, but also has build people to people communication, through project development and economic integration.